Do public information and subsidies contribute to the entrepreneurial environment? An exploratory translantic study with localglobal perspectives - Grimm, Heike (2006)
Variations in the economic performance of nations and regions due to an ongoing globalization and economic liberalization have fuelled debates about the role of public policies in economic growth. This article contributes to the empirical debate on the role of public policies in stimulating start-ups and regional economic growth by looking at public information, public counseling services, and public start-up assistance programs for entrepreneurs in the United States and Germany. The goal of the qualitative cross-national study is to evaluate potentials of public support for entrepreneurs in a global environment. - Reproduced.
Keywords: Public policy